Does Coordination of Macro Policies Enhance Economic Growth? Evidence From West Africa - Ephraim Ugwu; Christopher Ehinomen; Julius Ibitoye; Adeleke Omolade (Universitas Airlangga, 2026)
Objective: In West Africa, poor macroeconomic policy coordination among the managers of the economy has negatively impacted the macroeconomic stability of the region as well as the economic growth. This study investigates macro policies coordination and its impact on economic growth in West Africa, using a panel data set of 15 countries from 1980 to 2021. Design/Methods/Approach: Vector Autoregression (VAR) is used for evaluation. The study used descriptive statistics and panel unit root tests. An optimal lag length was selected based on five criteria, and the impulse response and Variance Decomposition were used for analysis. Findings: The panel stationarity tests reveal that the variables are stationary in first differences at the 5% significance level. The impulse response functions of the log of GDP to inflation showed a negative shock in the short and medium runs, and a positive shock in the long run. The response to the log of broad money supply indicates a positive response in both the short, medium, and long-run. The response to capital expenditure indicated a positive short-run effect, followed by a negative shock in the medium and long runs. While the trade policy variable indicated a positive response in the short, medium, and long run. The variance decomposition of the log of GDP showed that apart from its own variation, it can only be explained by a variation in broad money supply. Originality/Value: This study contributes to the existing literature by evaluating the coordination of macroeconomic policies across the member states of ECOWAS in both the short and long run for macroeconomic stabilization in the region. The implication of considering key macroeconomic factors will help in generating results for more reliable economic analysis and forecasts. Practical/Policy implication: The study therefore recommends tight fiscal measures and monetary policy expansion, as these would enhance growth in the region